Social Expenditures at Sub-National Level: An Experience from Indian state of Odisha - Pareswar Sahu; Sushanta Kumar Mahapatra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
The composition and trends of social expenditures at sub-national level in India has been examined using the secondary data from 1987-88 to 2013-14 of the state of Odisha. The composition shows (1) the insignificant share of productive social expenditures, (2) significant share of education relegating the role of health care and (3) higher priority of transfer payments relative to the level of employment and health. The comparative analysis of the composition between pre and post-restructuring period indicates the shifting of priority from education and health towards transfer payments in the later than the former period. The level of social expenditures has been declined over the time period leading to excessive contraction of educational expenditures. The decline in the level of social expenditures is attributed to the use of implicit loopholes of the efficiency criteria used for the devolution of federal transfers. For the economic development of the state increased level of social expenditures, higher priority of education and health and reform in the efficiency criteria used for the devolution of transfers are of crucial need of the hour.
Keywords: I32; I10; I20; H10; G10; 330